2017
DOI: 10.4314/ahs.v17i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Developmental screening: predictors of follow-up adherence in primary health care

Abstract: Background: The importance of early identification for infants and young children with developmental delays is well established. Poor follow-up on referrals, however, undermines the effectiveness of early intervention programmes. Objectives: To identify factors, including text message reminders, that influence follow-up adherence for early intervention after developmental screening in primary health care. A secondary objective surveyed reasons for follow-up default. Methods: The PEDS tools were used to screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The final point in the screening process that has the potential to impact parental screening experiences are follow‐up procedures after the screening (Schoeman, Swanepoel, & Van der Linde, 2017). The majority of caregivers noted that they received no formal follow‐up after their screening.…”
Section: Discussionmentioning
confidence: 99%
“…The final point in the screening process that has the potential to impact parental screening experiences are follow‐up procedures after the screening (Schoeman, Swanepoel, & Van der Linde, 2017). The majority of caregivers noted that they received no formal follow‐up after their screening.…”
Section: Discussionmentioning
confidence: 99%
“…The study was not powered, nor was it of sufficient duration, to detect a difference in rates of diagnosis of ASD. We may anticipate that ASD detection will improve, but the 57.0% response rate from physicians, combined with the poor follow-through by parents, 40 will attenuate the effect of universal screening.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental screening administered by CCWs in the home setting has shown to have a positive impact on follow-up adherence for rescreen. Transportation costs can impede attendance to PHC facilities (Schoeman, Swanepoel, & van der Linde, 2017). However, mHealth allows for the screen to take place at home, where only the caregiver is relied upon being present for the screening.…”
Section: Ccws' Perceptionsmentioning
confidence: 99%
“…Studies reported poor follow-up adherence of high risk families to PHC settings primarily due to logistical reasons and employment responsibilities (Giannoni & Kass, 2010;Schoeman et al, 2017). For this reason, mHealth screening in the home-setting may be an adequate model for service delivery in terms of early detection and close developmental surveillance.…”
Section: Ccws' Perceptionsmentioning
confidence: 99%